2005
DOI: 10.1120/jacmp.2025.25352
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dose-Area Product with GafChromic XR Type R Film

Abstract: Many of the newer X‐ray machines are equipped with electronic means to provide dose–area product (DAP) information. For machines without that ability, an alternative method is to record radiation on a film that can handle a large amount of cumulative exposure. The use of GafChromic XR Type R film was investigated for this purpose by placing it at the X‐ray tube assembly to record the radiation in interventional radiological procedures. Dose‐area product was determined with a reflective densitometer and then wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
(11 reference statements)
1
12
0
Order By: Relevance
“…This was consistent with other reported coefficients of variation for flatbed scanners of 1.8% (Thomas et al 2005). …”
Section: Psd Monitoringsupporting
confidence: 93%
“…This was consistent with other reported coefficients of variation for flatbed scanners of 1.8% (Thomas et al 2005). …”
Section: Psd Monitoringsupporting
confidence: 93%
“…Without a direct comparison it is difficult to confirm whether there is an increased dose response for this film over the obsolete XR model. Perhaps the best comparison is with the work by Thomas et al 16 who provided pixel value responses versus air kerma as was presented in this paper. They reported that the film was usable up to 6 and 14 Gy for document scanners and densitometers, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Its performance characteristics, especially its sufficient wide latitude (range of dose response) and utility have been verified in our earlier publications (Thomas et al , 2005. We had used this recording media to study the radiation dose in interventional radiology (Chu et al 2006).…”
Section: Methodsmentioning
confidence: 96%